Diabetes mellitus in a young Amazon Indian child - Gabbay, Mônica Andrade Lima; Bussad, Edson; Persoli, Ligia; Volpini, Walkiria; Dib, Sergio Atala (São Paulo Medical Journal, 2005)
CONTEXT: Although type 2 diabetes has been described among American Indian children, no case of type 1 diabetes has been reported in the literature. CASE REPORT: We report the ﬁrst case of diabetes in a South American Indian child from the tropical rainforest, who was positive for IA2 autoantibodies and genetic markers of susceptibility to type 1 diabetes, but also demonstrated residual beta cell function four years after diagnosis.